New Directions In Professional Development - Novick, Rebecca (Education Policy Analysis Archives, 1996)
There is increasing recognition that school reform and staff development are integrally related. Yet, despite a rich literature on adult learning and human development which supports teachers' need for a wide array of opportunities to construct their own understandings and theories in a collaborative setting, top down mandates have frequently left teachers out of the reform process. It is argued here that effective staff development should be tied directly to the daily life of classroom and grounded in the questions and concerns of teachers. Both a theory of pedagogy that advocates teaching for understanding and learning as understanding and a model of staff development based on practical knowledge enriched by critical reflection are discussed.